Learning Transfer Exploration Model from Skill Institute to Workplace, PLS-SEM Approach - Yunus, Faizal Amin Nur; Razali, Nizamuddin; Mohd Affandi, Haryanti; Kamis, Arasinah; Rahim, Mohd Bekri; Rozali, Mohd Zulfadli; Sulaiman, Junita (Journal of Technical Education and Training, 2021)
Skills and job mismatch issues have become common and recurring issues in Technical and Vocational Education Training (TVET). This issue is associated with the transfer of learning that involves various factors such as the area of training, certification level, curriculum, instructors, facilities and resources and industry recognition. In line with the Baldwin & Ford model, learning transfer involves three major factors such as the trainee’s characteristics, the training design and working environment. Therefore, identify the factors which contribute to the effective transfer of learning is necessary. This study attempts to identify which factors are contributing to learning transfer based on National Occupational Skill Standard (NOSS) system in skill institutes in Malaysia to workplace. This is because the lack of relevant studies related to the learning transfer on the NOSS system and at once makes it difficult to emphasize the factors to be considered for effective transfer of learning. The design of the survey study through the distribution of questionnaires to 309 Malaysian Skills Certificate trainees was done to generalize the study findings. This study used the Partial Least Squares-Structural Equation Modeling (PLS-SEM) tool to validate the model. PLS-SEM is choose because it can predict and explain constructs target. Then it can explore the relationship between the construct. Besides that, PLS SEM is chosen because this method can be done on complex structure equation model that consists more constructs and indicators. PLS-SEM can also control both a reflective and formative constructs. Findings indicate that work environment and training design positively influences learning transfer be represented by generalization and retention construct. The findings provide useful insight and information regarding the learning transfer that correlate with mismatch issues that policy makers, training provider, employers and trainees need to consider to produce highly skill workers subsequently completed this skills mismatch issue.